Autoimmune haemolytic anaemia and thrombocytopaenia in a single-centre cohort of patients with systemic lupus erythematosus from Turkey: clinical associations and effect on disease damage and survival. (October 2019) - Artım-Esen, B; Çene, E; Şahinkaya, Y; Erdugan, M; Oğuz, E; Gül, A; Öcal, L; İnanç, M
Introduction: Thrombocytopaenia and autoimmune haemolytic anaemia (AIHA) have considerable impact on prognosis in systemic lupus erythematosus (SLE). We investigated the frequencies of these haemocytopaenias, along with their associations and effect on outcome in a single-centre cohort of patients with SLE. Methods: Demographic characteristics, clinical features, autoantibody profiles, damage and mortality data were compared between patients with and without each haematological abnormality. Variables displaying significant differences between the groups were entered into logistic regression. Results: Ninety-three patients had AIHA and 215 had thrombocytopaenia. Both were associated with neuropsychiatric (NP) involvement, with each other, leucopaenia, antiphospholipid syndrome (APS) and antiphospholipid antibodies. More patients in both groups had organ damage, and their damage scores were higher. Association to NP damage was discernible. In addition, cardiovascular and renal damage and diabetes were more pronounced in patients with thrombocytopaenia. At logistic regression analysis, younger age, anticardiolipin antibody IgM positivity, leucopaenia and thrombocytopaenia were associated with AIHA whilst lupus anticoagulant activity, AIHA, leucopaenia, APS and NP involvement were associated with thrombocytopaenia. Among damage items, peripheral vascular damage, diabetes, NP damage, renal and ocular damage displayed significant associations with thrombocytopaenia, whereas none of the items did with AIHA. Patients with AIHA had significantly reduced survival rates at 10 and 20 years. Conclusions: We observed that AIHA and thrombocytopaenia were associated with severe lupus, affecting major organs and causing end organ damage. Thus, they may be considered as prognostic markers. Furthermore, AIHA and especially thrombocytopaenia may also be a marker for a subgroup of lupus patients who have or may develop APS.